MARKETING STRATEGY OF PEEL OFF FACE MASK FROM GELATIN (Case Studies at Sistmask Online Stores) - B., Driani,; Putri, B.R.T.; Sukanata, I W. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study aims to analyze the internal and external environmental factors in the Sistmask Online Store business that affect the marketing of  peel off  face masks from gelatin, determine the business position of the Sistmask Online Store in the industry and formulate the right marketing strategy for the Sistmask Online Store business. This research is a case study conducted in the Sistmask Online Store. The number of consumer and non-consumer respondents was 90 people and expert respondents were 3 people. The data sources used are primary and secondary data. Data were collected through observation,  indepth interviews  and interviews with the help of questionnaires. There are 4 analyses used, namely, 1) internal and external analysis of efforts to find factors of strengths, weaknesses, opportunities and threats that will be included in the IFE and EFE matrices; 2) the IE matrix used to determine the position of the business; 3) SWOT analysis is used to formulate alternative business marketing strategies and 4) QSPM analysis is used to determine the priorities of marketing strategies. The results of the IFE and EFE analysis of the business obtained products made of organic basic materials (major strength), did not have a clear vision and mission (main weaknesses), the trend of wearing face masks using organic materials (major opportunities) and the existence of BPOM certificate raids (the main threat). This study shows that the business position of the Sistmask Online Store is in cell V (maintain and maintain) in the IE matrix with an IFE value of 2.89 and an EFE value of 2.90 with the main priority strategy is to Strive for product development on a regular basis